2020
DOI: 10.3390/f11050537
|View full text |Cite
|
Sign up to set email alerts
|

Drought Primarily Reduces Canopy Transpiration of Exposed Beech Trees and Decreases the Share of Water Uptake from Deeper Soil Layers

Abstract: Research Highlights: During drought, reduced soil water availability and increased vapor pressure deficit diminished transpiration in a mature beech stand (Fagus sylvatica L.). Dominant trees were more affected than suppressed trees. The share of soil water uptake from deeper layers decreased. The ability of individual trees in the forest stand to save water during drought was apparently dependent on their social status. This would be relevant for forest management. Objectives: We investigated which basal area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 55 publications
0
10
1
Order By: Relevance
“…Soil and stem oxygen and hydrogen isotope sampling with moderately high resolution (2–4 d wk −1 ) in a subtropical conifer plantation revealed that tree water sources shifted to deeper soil layers with a seasonally progressing drought (Yang et al ., 2015 ). However, these results contrast with the findings of Lüttschwager & Jochheim ( 2020 ). They applied a mechanistic ecosystem model revealing that in the drought year 2003 beech trees not only reduced total water use but also decreased the relative water uptake from deeper soil layers.…”
Section: Introductioncontrasting
confidence: 97%
“…Soil and stem oxygen and hydrogen isotope sampling with moderately high resolution (2–4 d wk −1 ) in a subtropical conifer plantation revealed that tree water sources shifted to deeper soil layers with a seasonally progressing drought (Yang et al ., 2015 ). However, these results contrast with the findings of Lüttschwager & Jochheim ( 2020 ). They applied a mechanistic ecosystem model revealing that in the drought year 2003 beech trees not only reduced total water use but also decreased the relative water uptake from deeper soil layers.…”
Section: Introductioncontrasting
confidence: 97%
“…For example, S Fu et al used sapwood area as a spatially scalar quantity to derive the transpiration water consumption of farmland protection forests in the oasis of Xinjiang [33]. D Lüttschwager et al used basal area as a spatially scalar quantity to analyze and derive a water saving strategy for beech stands in arid regions of northern Germany [34]. In their study, Yue G et al used leaf area as the expanded scalar quantity to scale the water consumption of the Caragana microphylla shrub community in Horqin Sandy Land [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, forests can conserve water and will not immediately experience a water shortage in the case of rainfall deficiency. During drought, forests with deep roots can take water from deeper soil layers [45], so the LE-H decrease is low. In contrast, grass, shrub, and soybean cannot conserve water.…”
Section: Effect Of Climate Variability On Surface Energy Balancementioning
confidence: 99%